Severe head injury in children: geographical range of an emergency neurosurgical practice. Issue 4 (18th June 2004) - Tasker, R C; Gupta, S; White, D K
Abstract : Objective: To determine the timings of regional transfer for emergency neurosurgery and intensive care after severe head injury in children, and the effective operational range of a regional service. Design: Prospective observational study of admissions to a regional paediatric intensive care unit (PICU). Setting: East Anglia region in England, January 2000 to December 2001, where 18 referring hospitals are within two hours road transit time from the centre. Patients: 69 severely head injured children (52 boys and 17 girls, aged 8.4 (3.6 to 12.5) years). Main outcome measures: Time interval between injury and arrival at first hospital (primary transfer); timing between arrival at first hospital and arrival in PICU or the operating theatre (secondary transfer). Results: Arrival in one of the 19 accident and emergency departments occurred (median, IQR) within 48 (35 to 70) minutes of the accident. After arrival, the interval of secondary transfer was 4.4 (3.2 to 5.8) hours. Children rarely received their surgery within four hours of injury; for this to occur, the geographical range of this regional practice would need to be restricted to those hospitals within about 45 minute road transit time from the centre. Conclusions: Good evidence supporting the recommendation that acute neurosurgery for the evacuation of a haematoma within four hours of injury is still scarce. The timings of care after an accident suggest that this guideline is unworkable in regions covering areas with road distance travel times in excess of 45 minutes.